Readers’ advisory guide development for webtoon - Hyerim Cho; Denice Adkins; Hillary Gould; Katy Bond; Ky Flood (Information Research: An International Electronic Journal)
Introduction. Readers’ advisory (RA) services are one of the core information services that libraries provide. As the types and formats of the collection materials have diversified, relevant RA services have evolved accordingly. This project develops an RA guide for webtoons, emerging online webcomics that have successfully engaged international audiences with their diverse themes and accessible content.